Current perceptions and working time models of female urologists in Germany: results of a large-scale survey - Hofer, Sarah; Welte, Maria-Noemi; Knipper, Sophie; Siech, Carolin; Greiser, Eva Maria; Wiemer, Laura Elisa; Müller, Karina; Bellut, Laura Claudia; Herlemann, Annika; Schönburg, Sandra; Walach, Margarete (World journal of urology, 2023)
Female urologist · Working time models · Part-time work · Survey
Online veröffentlicht: 13. September 2023
Gesehen am 20.11.2023